Management by geographical area or management specialised by disorder? : a mixed-methods evaluation of the effects of an organisational intervention on secondary mental health care for common mental disorder /: a mixed-methods evaluation of the effects of an organisational intervention on secondary mental health care for common mental disorder. (March 2016) - Tulloch, Alex D
No abstract available